Secondary Growth and Carbohydrate Storage Patterns Differ between Sexes in Juniperus thurifera - DeSoto, Lucía; Olano, José M.; Rozas, Vicente (Frontiers in Plant Science, 2016)
Differences in reproductive costs between male and female plants have been shown to foster sex-related variability in growth and C-storage patterns. The extent to which differential secondary growth in dioecious trees is associated with changes in stem carbohydrate storage patterns, however, has not been fully assessed. We explored the long-term radial growth and the seasonal variation of non-structural carbohydrate (NSC) content in sapwood of 40 male and 40 female Juniperus thurifera trees at two sites. NSC content was analyzed bimonthly for one year, and tree-ring width was measured for the 1931–2010 period. Sex-related differences in secondary growth and carbohydrate storage differed between sites. Under less restrictive environmental conditions females grew more and stored more non-soluble sugars than males. Our results reinforce that sex-related differences in growth and resource storage may be a consequence of local adaptation to environmental conditions. Seasonal variation in soluble sugars concentration was opposite to cambial activity, with minima seen during periods of maximal secondary growth, and did not differ between the sexes or sites. Trees with higher stem NSC levels at critical periods showed higher radial growth, suggesting a common mechanism irrespective of site or sex. Sex-related patterns of secondary growth were linked to differences in non-soluble sugars content indicating sex-specific strategies of long-term performance.